Teachers Who Grow As Collaborative Leaders - Richard D. Sawyer (Arizona State University, 2001)
The following narratives examine three teachers over a course of ten years as they first entered teaching and began to collaborate with other teachers on curriculum. Specifically, the study examines how the teachers 1) developed as collaborators and 2) perceived elements of support from both within and outside the classroom for their collaborative efforts. The article argues that the successful collaborative efforts helped deepen their sense of agency and initiative within their teaching and, to a lesser degree, stimulated reform and change within their schools. In turn and to varying degrees, the process of collaboration supported their personal renewal in their work. The article suggests that structural support for these teachers that connected to their emerging personal practical knowledge was crucial for their development as teacher collaborators. The article concludes by suggesting how schools may be restructured to start to become sites of authentic leadership that build on the talents, meaning, voice, and knowledge of teachers.